2008
DOI: 10.1590/s0100-204x2008001000001
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do algodoeiro Bt na dinâmica populacional do pulgão-do-algodoeiro em casa de vegetação

Abstract: Resumo -O objetivo deste trabalho foi desenvolver um protocolo experimental para avaliar o impacto do algodoeiro Bt na bionomia e na escolha de plantas para colonização pelo pulgão-do-algodoeiro (Aphis gossypii). A bionomia do pulgão foi avaliada em casa de vegetação com insetos criados em gaiolas individuais com plantas de algodão Bt, da variedade DP 404 BG (Bollgard), ou sua isolinha não transformada DP 4049. Gaiolas contendo vasos com plantas de algodoeiro Bt e não-Bt foram usadas como arena de escolha, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
4
1
3
Order By: Relevance
“…Contrasting with those results, Sisterson et al (2004) found no significant differences in mortality among aphids fed transgenic cotton, and Sujii et al (2008) found that Bt cotton does not significantly affect aphid life cycle, survival, fecundity and colony formation. Research carried out by Deng et al (2003), however, put forth convincing evidence that aphid populations on Bt cotton are consistently larger than those on conventional cotton.…”
Section: Introductioncontrasting
confidence: 61%
“…Contrasting with those results, Sisterson et al (2004) found no significant differences in mortality among aphids fed transgenic cotton, and Sujii et al (2008) found that Bt cotton does not significantly affect aphid life cycle, survival, fecundity and colony formation. Research carried out by Deng et al (2003), however, put forth convincing evidence that aphid populations on Bt cotton are consistently larger than those on conventional cotton.…”
Section: Introductioncontrasting
confidence: 61%
“…Embora existam pesquisas visando ao controle alternativo do afídeo (ANDRADE et al, 2012;ANDRADE et al, 2013;BORTOLI et al, 2015;SUJII et al, 2008) em algodoeiro, tem-se observado, frequentemente, que o uso dos agroquímicos como única ferramenta de controle está dificultando o manejo da praga. Isto por selecionar indivíduos com resistência a esses produtos, provocar a sua ressurgência e favorecer o escape dos afídeos de seus agentes de controle natural, pela morte destes em decorrência da utilização massiva de inseticidas sintéticos, em sua maioria, não seletivos (PESSOA et al, 2004).…”
Section: Estudo Da Unidade Amostral Para a Gossypii Em Algodoeirounclassified
“…Bollgard â II provides slightly better control, and Widestrike © is quite effective against this pest. Other primary pests such as cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) (Sujii et al, 2008(Sujii et al, , 2013 and the boll weevil, Anthonomus grandis Boheman (Sujii et al, 2013) are unaffected by Cry1Ac and may increase in numbers due to a potential reduction in the use of pesticides. Bollgard â II and Widestrike © also do not control the non-lepidopteran primary pests of cotton in Brazil, which has limited their acceptability.…”
Section: Introductionmentioning
confidence: 99%